A diamond-like cuprous coordination polymer based on the [Cu8I6]2+ cluster with multistimuli-responsive luminescence and iodine adsorption behavior. Issue 10 (21st February 2022) - Zheng, Han-Wen; Yang, Dong-Dong; Liang, Qiong-Fang; Liu, Yan-Ping; Shan, Jia-Hui; Liu, Qian-Qian; Tan, Hong-Wei; Chen, Ling; Zheng, Xiang-Jun
Abstract : A diamond-like cuprous coordination polymer based on the [Cu8 I6 ] 2+ cluster has been successfully synthesized. This complex exhibits thermochromic and mechanochromic luminescence properties as well as good performance for the sorption and release of I2 . Abstract : Copper(i ) iodide-based compounds can exhibit interesting multistimuli-responsive behaviors and have attracted great interest due to their widespread applications. In this study, a novel copper(i ) complex, formulated as [Cu8 I6 (CN)2 (PPh3 )4 ] n (1 ) with the [Cu8 I6 ] 2+ cluster as a secondary building unit, is reported. The synthesis, structure, photoluminescence, and the sorption and release of I2 were investigated in detail. The selection of the non-centrosymmetric bridging ligand CN − and the tetrahedral coordination geometry of Cu(i ) result in a diamond-like framework of complex 1 with nonlinear optical properties. Complex 1 exhibits ultralong luminescence with a temperature-dependent afterglow color change, which can be attributed to the modifications and transitions of different energy states. Upon mechanical grinding, 1 also exhibits redshifted emission from cyan-yellow to dark-red due to the transformation from a crystalline state to an amorphous state. In addition, 1 has good adsorption and desorption processes of I2 due to the weak interaction of I2 with coordinated I − in the framework.